Artificial Intelligence literacy in language classroom in Malaysia - Bizami, Najwa Amanina; Johar, Nurul Atiqah (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2025)
Fostering AI literacy in language classrooms is essential, as AI tools are increasingly integrated into learning both inside and outside the classroom (Ng et al., 2021). Educators should equip students not only to use AI tools like chatbots, pronunciation trainers, and conversational agents for speaking practice but also to critically evaluate outputs, detect bias, and apply AI responsibly (Szoke & Menyhei, 2025). While these tools provide instant feedback and low-stakes practice, a lack of AI literacy may lead students to overtrust AI, potentially hindering the development of their own metacognitive speaking strategies.